On the problems of the home country control - David Mayes; Jukka Vesala (Bank of Finland, 1998)
In the European Economic Area the home country supervises the activities of its banks, wherever they are operating via branches or across borders, while the host country handles the stability of its financial system and problems stemming from failure or distress.We address two main problems related to the conduct and co-ordination of these two responsibilities.First, the introduction of the euro and the removal of other regulatory barriers is likely to lead to increasing internationalization of banking.In particular in smaller countries, large portions of the banking sector may be supervised by other 'home' authorities.This will make difficult assessing what is happening in, the market as a whole and warning about emerging systemic problems.Home supervisors will find it difficult to cover the widening range of countries in which their banks operate.Increasing the information exchanged and co-operation among supervisors would be helpful, but emphasizing public disclosure by banks to enable market discipline to supplement the work of the authorities would help overcome the problem of information considerably, in addition to the favourable impact on incentives to banks for prudent risk management.Second, the interests of home and host supervisors in a crisis may differ and need to be co-ordinated.What is important to the host authority in. a small country may be inconsequential to the home supervisor of a multinational bank in a large country.Coordination at European level might help.
URN:NBN:fi:bof-20140807501
Keywords: 330; banking supervision; disclosure; crisis management